Combined Amperometry and Electrochemical Cytometry Reveal Differential Effects of Cocaine and Methylphenidate on Exocytosis and the Fraction of Chemical Release. (18th February 2019) - Zhu, Wanying; Gu, Chaoyi; Dunevall, Johan; Ren, Lin; Zhou, Xuemin; Ewing, Andrew G.
Abstract: Amperometry with nanotip electrodes has been applied to show cocaine and methylphenidate not only trigger declines in vesicle content and exocytotic catecholamine release in a model cell line but also differentially change the fraction of transmitter released from each individual vesicle. In addition, cocaine accelerates exocytotic release dynamics while they remain unchanged after methylphenidate treatment. The parameters from pre‐spike feet for the two drugs are also in opposition, suggesting this aspect of release is affected differentially. As cocaine and methylphenidate are psychostimulants with similar pharmacologic action but have opposite effects on cognition, these results might provide a missing link between the regulation of exocytosis and vesicles and the effect of this regulation on cognition, learning, and memory. A speculative chemical mechanism of the effect of these drugs on vesicle content and exocytosis is presented. Abstract : Alles im Kopf : Mittels Einzelzellamperometrie und intrazellulärer elektrochemischer Vesikelstoßzytometrie wurden die Auswirkungen von Kokain und Methylphenidat auf Exozytose und die Freisetzung chemischer Stoffe in PC12‐Zellen untersucht. Die beiden Wirkstoffe zeigen einen unterschiedlichen Einfluss auf die Dynamik der Exozytose und den Anteil freigesetzter Stoffe.